2021
DOI: 10.1136/jitc-2020-002232
|View full text |Cite
|
Sign up to set email alerts
|

IL-15 mediated expansion of rare durable memory T cells following adoptive cellular therapy

Abstract: BackgroundSynovial sarcoma (SS) and myxoid/round cell liposarcoma (MRCL) are ideal solid tumors for the development of adoptive cellular therapy (ACT) targeting NY-ESO-1, as a high frequency of tumors homogeneously express this cancer-testes antigen. Data from early phase clinical trials have shown antitumor activity after the adoptive transfer of NY-ESO-1–specific T cells. In these studies, persistence of NY-ESO-1 specific T cells is highly correlated with response to ACT, but patients often continue to have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…The dynamic of serum MCP1 concentration change is earlier than the other cytokines, suggesting MCP1 was induced by lymphodepletion rather than CAR T-cell infusion, which is consistent with human study showing that high MCP1 concentration at the time of CAR T-cell infusion correlates with better outcome (37). This observation further supports the relevance of the canine model to clinical study of human CAR T cells (38). Our results in healthy dogs also provide baseline comparison for future patient dog treatment to distinguish immune response against immunotherapy from that against tumor cells.…”
Section: Discussionsupporting
confidence: 85%
“…The dynamic of serum MCP1 concentration change is earlier than the other cytokines, suggesting MCP1 was induced by lymphodepletion rather than CAR T-cell infusion, which is consistent with human study showing that high MCP1 concentration at the time of CAR T-cell infusion correlates with better outcome (37). This observation further supports the relevance of the canine model to clinical study of human CAR T cells (38). Our results in healthy dogs also provide baseline comparison for future patient dog treatment to distinguish immune response against immunotherapy from that against tumor cells.…”
Section: Discussionsupporting
confidence: 85%
“…Endogenous NY-ESO-1 specific T cells have been safely transferred in a phase I trial; however, all patients experienced disease progression and transferred cells lacked markers of proliferation or activation [30,74 ▪ ]. Proliferation was induced when the T cells were cultured ex vivo with IL-15, supporting the evaluation of this cytokine for use following cell infusion to support responses.…”
Section: Cancer Testis Antigensmentioning
confidence: 99%
“…IFNα has been safely utilized in TIL therapy, and IFNγ may indeed have its uses in sensitizing patients to ACT [95], but should be evaluated in the medium – to long term after cell infusion, for example several weeks after or at the time of progression. Ex-vivo application of IL-15 has stimulated activation and proliferation of persisting NY-ESO-1 endogenous T cells supporting its clinical evaluation as a sensitizing agent [74 ▪ ]. Importantly, high dose IL-2 was utilized following cell infusion in early trials of NY-ESO-1-directed TCRs and warrants further consideration once the safety and activity of this approach has been reliably demonstrated [69,70].…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, they concluded that durvalumab together with anthracycline-/taxane-based neoadjuvant chemotherapy (NACT) was the most optimal treatment regime for increased pCR rates. Additionally, more advanced molecular analysis such as RNA sequencing was also often used as biomarker discovery 242 , 265 , 266 . For instance, Pusztai et al (Yale Cancer Center, New Haven, CT, USA) found while investigating paclitaxel in combination with durvalumab and the poly-ADP ribose polymerase (PARP) inhibitor olaparib in breast cancer that their dendritic cell signature had a positive correlation with pCR in the treatment arm 267 .…”
Section: Finalized Clinical Studiesmentioning
confidence: 99%